Internet Of Things Based Pest And Growth Management System Using Natural Pesticides & Fertilizers For Small Scale Organic Farming (Journal of Pharmaceutical Negative Results, 2022)
AbstractPesticides is a biological agent such as antimicrobial, virus, disinfectant or bacterium that incapacitates, deters, kills pests and protect humans from vector-borne diseases such as schistosomiasis, malaria, dengue fever etc. Human health is at danger due to the extreme use of pesticides on plants which also cause rigorous effects on the environments too. Pesticides can cause chronic adverse health effects as well as acute adverse health effects that can take place months or years after revelation. In addition, intentional, unintended or high occupational exposure to pesticides can end result in hospitalization and death. Organic farming is a holistic production management system that uses ecologically based biological fertilizers and pesticides derived mainly from plant wastes, animal and cover crops from nitrogen-fixation. Organic farming uses smaller quantity of pesticides, decrease nitrate leakage into surface water and groundwater, reduces erosion of soil and recycles cattle’s wastes back into the farm. Because of environmentally friendly nature of the organic farming it is measured as a feasible alternative in contrast to chemical based farming. Additionally, to pesticides, organic pest control incorporates cultural, genetic and biological controls to diminish pest damage. The advantages the farmers are gaining by adapting the IoT program are twice. It has helped farmers raise crop yields and cut costs. IoT is intimately related to automation, so it requires fewer workers and not as much of human interaction. IoT in organic farming allows obstacles to be removed and all the issues that take place throughout farming processes to be minimized. IoT plays a most important role in detecting the pest infections at the correct time to avoid this crisis. In this paper, We have proposed IoT based pest & growth management system using natural pesticides and fertilizers. IoT based pest management system using organic pesticides involves the acceptance of ecologically sound and scientifically strategies as precise by the international and national organic production standards. This method promotes the development of the plant with enriched vitamins as well as other health factors in the productions of plant.